Analisis Pengaruh Promosi pada Digital Wallet Terhadap Konsumsi Masyarakat Muslim di Gresik - Amrullah, Habib; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2022)
Gresik is one of the districts in the east java province with a large population, especially those who are Muslim. The purpose of this study is to find out the effect of promotion on digital wallets on Muslim consumption in Gresik. Research subjects were taken using sampling methods and data sources in the form of primary and secondary. The validity test is conducted quantitatively through the SPSS application. The results of this study using a simple linear regression test showed the effect of promotion on digital wallets on the consumption of Muslim communities in Gresik. in the T hypothesis test, it shows that the promotion of digital wallets partially on the consumption of the Muslim community in Gresik. The results prove that promotion on digital wallets has a major contribution to Muslim consumption in Gresik, regardless of the digital wallet brand used or transactions made.